Clonal complexes of carbapenem-resistant Klebsiella pneumoniae recovered from community sewage. (12th January 2023) - Oliveira, Pâmela Maria; Faria-Junior, Célio; Silva, Daniely Martins; Matos, Larissa Fernandes; Pereira, Alex Leite
Abstract: Carbapenem-resistant Klebsiella pneumoniae (CR-Kp) are life-threatening multidrug-resistant bacteria. In this study, CR-Kp strains isolated from sewage treatment plants (STPs) ( n = 12) were tested for carbapenemase genes ( bla KPC, bla NDM, bla IMP, bla VIM and bla OXA-48 ) and had their sequence types (ST) and clonal complexes (CCs) defined. A collection of clinical CR-Kp strains recovered in local hospitals was added to phylogenetic analyses along with sewage strains in order to infer clonality among CR-Kp strains. A total of 154 CR-Kp strains were isolated from raw sewage [55.8% (86/154)], treated sewage [25.3% (39/154)] and from water body downstream from STPs [18.8% (29/154)]. No CR-Kp strain was isolated from upstream water samples. bla KPC or blaNDM were detected in 143 (92.8%) strains. The occurrence of blaKPC-or-NDM CR-Kp strains was positively associated with the number of hospitalized patients in the areas serviced by STPs. Eleven STs were detected in CR-Kp strains, most of them belonging to the clinically relevant CC11 [ST11 ( n = 13–28.2%) and ST340 ( n = 7–15.2%)]. CCs 11, 15, 17, 147 and 2703 are shared by clinical and sewage CR-Kp strains. In conclusion, sewage harbors clinically relevant clones of CR-Kp that resist sewage treatments, contaminating water bodies downstream from STPs. HIGHLIGHTS: Carbapenem-resistant Klebsiella pneumoniae (CR-Kp) was evenly detected in sewage and water collected downstream from sewage treatment plants. CR-Kp of genotype CC11- bla KPC2 is predominant in sewage. High-risk clonal complexes (CC) 11, CC15, CC17 and CC147 are shared by sewage and clinical CR-Kp strains. High-risk clones CC11- bla KPC-2 and CC147- bla NDM-1 were detected in treated sewage. Graphical Abstract